2015
DOI: 10.14260/jemds/2015/2397
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Lichtenstein Versus Des Arda Repair for Inguinal Hernia

Abstract: BACKGROUNDInguinal hernia repair is the most frequently performed operation in any general surgical unit. The Bassini's, Shouldice and other tissue-based techniques are still being acceptable for primary inguinal hernia repair. Desarda's technique is originally a tissue based hernia repair using an undetached strip of external oblique aponeurosis to strengthen the posterior wall of the inguinal canal. The aim of the present study was to compare Lichtenstein hernia repair and Desarda herniorrhaphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, Sowmya and Udapudi [23] found that recovery time after Desarda herniorrhaphy was much shorter than that following open hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sowmya and Udapudi [23] found that recovery time after Desarda herniorrhaphy was much shorter than that following open hernia repair.…”
Section: Discussionmentioning
confidence: 99%